Explaining hot spots of methane flux in a restored wetland: the role of water level, soil disturbance, and methanotrophy - Camilo Rey-Sanchez; Ariane Arias-Ortiz; Kuno Kasak; Robert Shortt; Daphne Szutu; Joseph Verfaillie; Thomas Lorenson; Martin Liira; Peeter Somelar; Mikk Espenberg; Dennis Baldocchi (Environmental Research Letters, 2025)
A high degree of uncertainty persists regarding current and future emissions of methane from both natural and constructed wetlands. Part of the problem is the existence of ‘hot spots’ of methane flux, which have not been clearly identified and studied at multiple scales. Methane has a short lifetime compared to carbon dioxide; thus, efforts to avoid methane hot spots from constructed wetlands can promptly decelerate the rate of atmospheric warming. In this study we measured methane fluxes using flux towers in a restored oligohaline wetland in the Sacramento–San Joaquin River Delta, where we previously identified a hot spot of methane flux using footprint-weighed flux maps and chambers. Our main objectives with this study were to determine why this hot spot occurs and what are the biogeochemical and microbiological conditions that lead to these high methane fluxes. We found four main mechanisms that explain the existence of the hot spot. (1) The hot spot was associated with areas where the water level was closer to the surface (2) Methane originated mostly from older unoxidized peat in deeper layers, which had a shorter migration pathway to the atmosphere at the hot spot location due to soil disturbance during wetland construction. (3) Relatively lower methane oxidation in the hot spot in the upper soil layer (10–30 cm under the surface), deduced from isotopic profiles in porewater carbon and upper-level methanotroph abundance. (4) Higher ebullition events at the hot spot that can be related to low water levels and lower bulk density throughout the soil profile. This study thus suggests that mitigating soil disturbances during wetland construction and managing water level can reduce the occurrence and magnitude of hot spots of methane flux in constructed wetlands.